Cyr Families of Saint Leonard Parent 130 ans d'histoire - Cyr, Marguerite
Contains the History and Geneology of St. Leonard Parent
D., 10/04
Keywords: Acadians -- New Brunswick -- History; Saint-Leonard-Parent Parish (N.B.); Saint John River Valley (Me. and N.B.) -- History; Saint Leonard (N.B.) -- History